1977
DOI: 10.1128/jvi.21.3.863-871.1977
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Sendai virus transcription: evidence for a single promoter in vivo

Abstract: The synthesis of Sendai virus RNA species was examined after UV irradiation of cells late in infection. Compared with the inactivation of 50S genomic RNA synthesis, the synthesis of the group of mRNA species that sediments at 18S was inactivated at an average rate consistent with a process of sequential transcription from a single promoter. The rates of inactivation of the synthesis of individual mRNA's separated by polyacrylamide gel electrophoresis confirmed this and, with the aid of additional data, suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
29
0
1

Year Published

1982
1982
1999
1999

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(35 citation statements)
references
References 42 publications
5
29
0
1
Order By: Relevance
“…Densitometric scanning showed that of the total transcripts, NP mRNA represented 49.3%; P, 15.6%; M, 8.2%; F, 10.3%; HN, 9.5%; and L, 7.0%. Thus, it seems that there is a polar effect on transcription in vitro as previously shown for other nonsegmented negative-strand RNA viruses (1,12,21,24). However the reason for inadequate synthesis of M protein mRNA in vitro is not clear.…”
Section: Figsupporting
confidence: 65%
“…Densitometric scanning showed that of the total transcripts, NP mRNA represented 49.3%; P, 15.6%; M, 8.2%; F, 10.3%; HN, 9.5%; and L, 7.0%. Thus, it seems that there is a polar effect on transcription in vitro as previously shown for other nonsegmented negative-strand RNA viruses (1,12,21,24). However the reason for inadequate synthesis of M protein mRNA in vitro is not clear.…”
Section: Figsupporting
confidence: 65%
“…Dead mice are marked by †. Wild-type 10 8 5/5 NT b 10 7 5/5 3/5 10 6 1/4 1.78 ϫ 10 6 2/5 3.16 ϫ 10 6 10 5 0/5 NT 10 4 0/5 0/5 SeVmSf 10 8 5/5 NT 10 7 5/5 5/5 10 6 5/5 7.94 ϫ 10 4 5/5 7.94 ϫ 10 4 10 5 3/5 3/5 10 4 0/5 0/5…”
Section: Discussionmentioning
confidence: 99%
“…There is only a single promoter at the 3Ј end of the viral RNA polymerase, comprising the P and L proteins (11). By recognizing the short conserved end (E) and restart (S) signals at each gene boundary, the polymerase gives rise to leader RNA and each mRNA (7). There is a trinucleotide intergenic sequence between the E and S signals, which is not transcribed (9,31).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…IrTadiation of NDV inactivates infectivity with single-hit kinetics (5,7,32,39) and blocks mRNA transcription (7). Recent irradiation studies have shown that the NDV genes are sequentially transcribed from a single promoter (9), as previously shown for Sendai virus (18) and vesicular stomatitis virus (VSV) (1,2). Genes for the three proteins associated with viral nucleocapsids (6,10,40), and thought to be involved in NDV-specific RNA synthesis, appear widely separated on the genome; those for the NP and P proteins are least sensitive to irradiation and thus closest to the promoter, whereas that for the L protein is as sensitive as infectivity and thus furthest from the promoter (9).…”
mentioning
confidence: 82%